EFFECTIVENESS OF TIOTRIAZOLINE IN COMPLEX THERAPY OF ISCHEMIC HEART DISEASE - E. A. Kartashova; A. A. Kastanyan; M. I. Nazheva; A. Yu. Zhulitov; E. I. Zheleznyak (Кардиоваскулярная терапия и профилактика)
Aim. To study molecular effects of tiotriazoline in 30 patients with stable angina I-III functional class.Material and methods. Comparison of molecular effects of cardioprotection is done based on dynamics of exercise tolerance dynamics, and via proteomic methods of investigation, questionnaires assessment of life quality in patients with ischemic heart disease (IHD).Results. It was found, that tiotriazoline improves exercise tolerance, shows strong cardioprotective effect that includes antioxidant and cytoprotection effects in IHD patients.Conclusion. Tiotriazoline helps to reduce the mean number of angina attacks in IHD patients, as to improve mean functional class.